Oral care practices carried out by nurses for orally intubated critically ill adult patients in Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan - Salim, Nursaliyana Ahmad (Universiti Sains Malaysia, 2013)
Oral hygiene or oral care is a fundamental aspect of nursing that impact on health, well-being and comfort of patients. Providing effective oral hygiene for patients in critical units is particularly challenging as the patient’s oral health may be compromised by medical conditions, treatment interventions, equipment and the patient’s inability to attend to his or her own oral care. This study was to identify the type and frequency of oral care, association between selected socio-demographic data (duration of working experience as a nurse), barrier in performing oral care with level of oral care performance for orally intubated critically ill patients in critical care unit of Hospital USM. A cross-sectional study was conducted on 120 nurses who worked in 1 Mutiara (ICU), 1 Fairuz (CCU), 2 Delima and 8 Selatan. Self-administered questionnaire was used and Chi-square test was employed to test the hypotheses in this study. Moreover, about 36 (30.0 %) nurse had working experience more than ten years as a critical care nurse. Most of the nurse having diploma education level which is 87 (72.5%). The results showed that the majority of the nurses had high level of oral care performance 98 (81.7%) and most of the oral care was performed in every 4 hourly that comprised of 58 (48.3%), type of oral care used is forceps and cotton 48 (40.0%) with the thymol gargle solution 97 (80.8%). There is an association between the duration of working experience and type and frequency of performing oral care with the level oral care practice where by p-value for each of the hypotheses is 0.043 (p<0.05) and p-value = 0.014 (p<0.05). Moreover, there is no association between barriers of oral care performance with the level of oral care practice which the p-value = 0.098 (p>0.05). As a conclusion, although most of the nurses have high oral care performance, there are still had some nurses who had low level of care practice. Therefore, the nurses should improve their level of performance by having oral care training course and include oral care education in nursing curricular.